Baffinella frigidus gen. et sp. nov. (Baffinellaceae fam. nov., Cryptophyceae) from Baffin Bay: Morphology, pigment profile, phylogeny, and growth rate response to three abiotic factors. Issue 5 (23rd August 2018) - Daugbjerg, Niels; Norlin, Andreas; Lovejoy, Connie
Abstract : Twenty years ago an Arctic cryptophyte was isolated from Baffin Bay and given strain number CCMP2045. Here, it was described using morphology, water‐ and non‐water soluble pigments and nuclear‐encoded SSU rDNA. The influence of temperature, salinity, and light intensity on growth rates was also examined. Microscopy revealed typical cryptophyte features but the chloroplast color was either green or red depending on the light intensity provided. Phycoerythrin (Cr‐PE 566) was only produced when cells were grown under low‐light conditions (5 μmol photons · m −2  · s −1 ). Non‐water‐soluble pigments included chlorophyll a, c 2 and five major carotenoids. Cells measured 8.2 × 5.1 μm and a tail‐like appendage gave them a comma‐shape. The nucleus was located posteriorly and a horseshoe‐shaped chloroplast contained a single pyrenoid. Ejectosomes of two sizes and a nucleomorph anterior to the pyrenoid were discerned in TEM. SEM revealed a slightly elevated vestibular plate in the vestibulum. The inner periplast component consisted of slightly overlapping hexagonal plates arranged in 16–20 oblique rows. Antapical plates were smaller and their shape less profound. Temperature and salinity studies revealed CCMP2045 as stenothermal and euryhaline and growth was saturated between 5 and 20 μmol photons · m −2  · s −1 . The phylogeny based on SSU rDNA showed that CCMP2045 formed a distinct clade with CCMP2293 and Falcomonas sp. isolated from Spain. Combining pheno‐ and genotypic data, the Arctic cryptophyte could not be placed in an existing family and genus and therefore Baffinellaceae fam. nov. and Baffinella frigidus gen. et sp. nov. were proposed.